Primary Papillary Serous Carcinoma of the Peritoneum, A Retrospective Analysis of 18 Cases - Taner Turan; Şadıman Altınbaş; Nurettin Boran; Gökhan Tulunay; Reyhan Öcalan; Figen Günday; Deniz Çavuşoğlu; Faruk Köse (Medical Network, 2006)
OBJECTIVE: Primary papillary serous carcinoma of the peritoneum (PPSCP) is an uncommon tumor. The aim of this study was to review of the patients with PPSCP. STUDY DESIGN: 18 women with PPSCP in gynecologic oncology clinic between 1995 and 2005 were retrospectively reviewed. RESULTS: At diagnose, one patient (5.5 %) had stage IV and other patients (94.5 %) were IIIC. Six patients received neoadjuvant chemotherapy (paclitaxel/platinum in 5 patients and cyclophosphamide/platinum in the other). Initial or interval optimal/suboptimal debulking surgery was performed in all patients. After surgery, all of the patients received adjuvant chemotherapy including paclitaxel/platinum (n=16) and cyclophosphamide/platinum (n=2). In 6 months after adjuvant chemotherapy, persistent, progressive or recurrence disease was detected in 8 patients (44.4%). In 9 patients (50%) recurrence was detected after 6 months. Clinical complete response to chemotherapy was 55.5%. Survival rate was 90%. CONCLUSION: PPSPC are frequently indistinguishable from advanced serous papillary carcinoma of the ovary. The treatment choice is optimal cytoreductive surgery with adjuvant chemotherapy, but although the radical treatment is used the survival rate is poor.